Phylogenetic Analysis of the Membrane Attack Complex/Perforin Domain-Containing Proteins in Gossypium and the Role of GhMACPF26 in Cotton Under Cold Stress - Chen, Pengyun; Jian, Hongliang; Wei, Fei; Gu, Lijiao; Hu, Tingli; Lv, Xiaoyan; Guo, Xiaohao; Lu, Jianhua; Ma, Liang; Wang, Hantao; Wu, Aimin; Mao, Guangzhi; et al. (Frontiers in Plant Science, 2021)
Membrane-attack complex/perforin (MACPF) domain-containing proteins are involved in various developmental processes, and in responding to diverse abiotic stress. The function and regulatory network of MACPF genes are rarely reported in Gossypium spp. Here, we gave the detailed identification and partial functional verification of the members of the MACPF family. Totally, 100 putative MACPF proteins containing complete MACPF domain were identified from four cotton species. They were classified into three phylogenetic groups, and underwent multifold pressure indicating that selection produced new functional differentiation. Cotton MACPF gene family members expanded mainly through whole genome duplication (WGD) /segmental, followed by the dispersed. Expression and cis-acting elements analysis revealed that MACPFs play a role in resistance to abiotic stresses, and some selected GhMACPFs were able to respond to the PEG and cold stresses. Co-expression analysis showed that GhMACPFs might interact with valine-glutamine (VQ), WRKY, and AP2/ERF domain-containing genes under cold stress. In addition, silencing endogenous GhMACPF26 in cotton by virus-induced gene silencing (VIGS) method indicated that GhMACPF26 negatively regulates cold tolerance. Our data provided a comprehensive phylogenetic evolutionary view of Gossypium MACPFs. MACPFs may work together with multiple transcriptional factors and play roles in acclimation to abiotic stress, especially cold stress in cotton.